Transient Effect at the Output of a Linear Dynamic System Controlled Pulse-Width Modulation - Petera, M. (Vysoké učení technické v Brně, Fakulta elektrotechniky a komunikačních technologií, 2015)
The goal of this work is to determine the size of overshoot produced at the output of a linear continuous second order system controlled by pulse width modulation. This work contains the calculation of the output signal response of the system in the time domain using the Laplace transform. The calculations of the amplitude of the output signal based on the pulse width modulation and system parameters are performed in this work. Finally the possibilities were given to determine the suitable period of pulse width modulation for required ripple. All the important calculations were compared with the simulations in the MATLAB-SIMULINK program and with the measurement at the real inertia second order cell.
Keywords: Pulse width modulation; Laplace transform; system; transfer function; signal; input; output; ripple